Randomised evaluation of pre-notification of trial participants before self-report outcome data collection to improve retention: SWAT86. Issue 4 (September 2022) - Sutton, Christopher J; Cotterill, Sarah; Forshaw, Denise; Rhodes, Sarah; Haig, Alexandra; Hammond, Alison
Background: Retention is considered the second highest trial methods priority in the UK after recruitment. There is limited evidence on whether notifying trial participants that a follow-up questionnaire will be sent soon ('pre-notification') affects retention. Methods: This Study Within a Trial (SWAT) evaluated whether sending a pre-notification letter or email around 2 weeks before sending a self-report questionnaire increased retention, in terms of provision of the host trial primary outcome. The SWAT was a randomised, two-arm, parallel-design (1:1 allocation ratio) trial, controlled by 'no pre-notification letter'. It was embedded within the WORKWELL host trial, which evaluated the impact of job retention vocational rehabilitation on work-related and health-related outcomes of employed people with inflammatory arthritis. The SWAT primary outcome was a valid response for the WORKWELL primary outcome. Results: Two hundred forty-four trial participants took part in the SWAT. All were included in the analysis. Among those sent a pre-reminder, 100/121 (83%) provided a valid response for the WORKWELL primary outcome, compared to 97/123 (79%) of those not sent a pre-reminder. The estimated adjusted odds ratio was 1.28 (95% confidence interval 0.67–2.42), with a risk difference of 3.8% (95% CI -6.1 to 13.6%), favouring the prereminder. The estimated intervention cost per additional participant retained was £53.42, and the total cost per additional participant retained was £46.52. Conclusion: Researchers may have a small improvement in trial retention by using pre-notification. The cost per additional participant retained is relatively low. However, further evaluations are merited.